The Authority of the Commercial Court in Bankruptcy Disputes - Royana Lumban Gaol (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The purpose of this study is to find out and understand the authority of the commercial court based on the application of Law Number 37 of 2004 in resolving bankruptcy disputes. This study uses descriptive analysis research techniques supported by a normative juridical approach. The results of the study show that legal considerations in a decision must be juridical and become the basis of a decision. Court decisions must contain certain articles of the relevant regulations and unwritten legal sources that are used as the basis for adjudicating, therefore the Commercial Court Decision at the Central Jakarta District Court Number 04/Pdt.Sus-Pailit/2016/PN.Niaga.Jkt. Pst is in accordance with Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations.